2016
DOI: 10.1136/neurintsurg-2016-012405
|View full text |Cite
|
Sign up to set email alerts
|

Venous sinus stenting in patients without idiopathic intracranial hypertension

Abstract: Dural venous sinus stenting may be an effective treatment for patients with symptomatic venous sinus stenosis without IIH in carefully selected cases, but may not be effective in resolving the symptoms of congenital hydrocephalus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 30 publications
0
18
0
Order By: Relevance
“…VSS is becoming an increasingly used treatment option for intracranial venous stenosis in the setting of IIH and related pathologies 1 6 12. Although other therapies are available, VSS is a reasonable alternative that may address a key pathophysiologic component in patients with IIH, demonstrable venous sinus stenosis, and an associated trans-stenosis pressure gradient.…”
Section: Discussionmentioning
confidence: 99%
“…VSS is becoming an increasingly used treatment option for intracranial venous stenosis in the setting of IIH and related pathologies 1 6 12. Although other therapies are available, VSS is a reasonable alternative that may address a key pathophysiologic component in patients with IIH, demonstrable venous sinus stenosis, and an associated trans-stenosis pressure gradient.…”
Section: Discussionmentioning
confidence: 99%
“…Pulsatile tinnitus itself has also been associated with TSS, independent of the presence of elevated intracranial pressure, and there are some data in the literature supporting the efficacy of transverse sinus stenting in this population . However, interpretation of these data is complicated by the fact that these studies did not assess for the presence of possible associated SSWA, despite the fact that studies have demonstrated a high prevalence of SSWA in this patient population.…”
Section: Introductionmentioning
confidence: 99%
“…11 A more comprehensive list of potential causes of PT is found in Table T1 I. Sigmoid sinus wall anomalies (SSWA) are an often unrecognized yet potentially treatable venous etiology of PT. 7,10,19,20,23 These include both sigmoid sinus diverticulum and sigmoid sinus dehiscence 19,20 Temporal bone and cerebellopontine angle vascular neoplasms 9 Fibromuscular dysplasia 14 Carotid artery stenosis or dissection 16 Aberrant carotid artery 16 and other middle ear vascular anomalies 18 Sigmoid sinus wall anomalies 7,10,19,20 Transverse sinus stenosis 21,22 Third mobile window syndromes 12 Conductive hearing loss 7 Acquired dural vascular lesions (malformations and fistulae) 8 Temporal bone and cerebellopontine angle vascular neoplasms 9 Fibromuscular dysplasia 14 Carotid artery stenosis or dissection 16 Aberrant carotid artery 16 and other middle ear vascular anomalies 18 Sigmoid sinus wall anomalies 7,10,19,20 Transverse sinus stenosis 21,22 Third mobile window syndromes 12 Conductive hearing loss 7 Eustachian tube dysfunction 7 Patulous Eustachian tube 17 Superior petrosal sinus-superior semicircular canal fistula ( Fig. 1 temporal bone computed tomographic (CT) scans performed for reasons other than PT 24 but are the most commonly identified radiographic abnormalities in CT...…”
Section: Introductionmentioning
confidence: 99%
“…Certain patients with symptomatic venous sinus stenosis without IIH may also benefit from stenting 3. Although the pathophysiology of IIH and venous sinus stenosis remains poorly understood, the available literature suggests that some patients have venous sinus outflow obstruction from sinus stenosis or occlusive arachnoid granulations that manifest as central cerebral venous hypertension.…”
Section: Introductionmentioning
confidence: 99%